The determinants and effects of training at work: Bringing the workplace back in - Philip J. O'Connell; Delma Byrne (The Economic and Social Research Institute (ESRI), 2009)
This paper brings together two research fields: on work-related training and high performance work practices (HPWP), respectively. We estimate models of both the determinants and the impact of training using the NCPP/ESRI Changing Workplace Survey. Our models of the determinants of training confirm previous research: age, education, contract, tenure, and firm size all influence training. Several components of HPWP are associated with a higher probability of training, specifically, general (non-firm-specific) training. Participation in general training is associated with higher earnings, as is involvement in highly participative and consultative working arrangements, and performance reward systems. These patterns of training, and returns to training, are broadly consistent with HPWP approaches and represent a challenge to human capital theory.
Keywords: 330; Betriebliches Bildungsmanagement; Weiterbildung; Bildungsverhalten; Bildungsertrag; Humankapital; Irland